Firm-level employment, labour market reforms, and bank distress - Moritz Stieglitz; Ralph Setzer (European Central Bank (ECB), 2019)
We explore the interaction between labour market reforms and financial frictions. Our study combines a new cross-country reform database on labour market reforms with matched firmbank data for nine euro area countries over the period 1999 to 2013. While we find that labour market reforms are overall effective in increasing employment, restricted access to bank credit can undo up to half of long-term employment gains at the firm-level. Entrepreneurs without sufficient access to credit cannot reap the full benefits of more exible employment regulation.
Keywords: G21; J21; J60; K31; 330; Structural Reforms; Bank Stress; Employment Protection; Unemployment Insurance